2011
DOI: 10.1021/je2006924
|View full text |Cite
|
Sign up to set email alerts
|

Stability Constants for the 18-Crown-6–Sodium Ion Complex in Mixtures of Water and Butan-1-ol or Butan-2-ol

Abstract: The complex formation constants of sodium ions with 18-crown-6 in mixtures of water and butan-1-ol or butan-2-ol at 298.15 K were determined by the potentiometric method with the use of sodium and chloride ion-selective electrodes. The correlations between the logarithm of the complex formation constants and the mole fraction of an alcohol in the mixed solvent were constructed based on the published data and the experimental results obtained in the present study. It was shown that the numerical value of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
1
1
Order By: Relevance
“…In summary, the MD data reveal that 18C6 nullifies the charge-enhancing effects of the SCA by eliminating charge trapping. Our results confirm the hypothesis stated in the introduction, i.e., the proposal that 18C6 binds charge carriers (Na + , NH 4 + , H 3 O + ) , and shuttles them through the SCA trapping layer.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…In summary, the MD data reveal that 18C6 nullifies the charge-enhancing effects of the SCA by eliminating charge trapping. Our results confirm the hypothesis stated in the introduction, i.e., the proposal that 18C6 binds charge carriers (Na + , NH 4 + , H 3 O + ) , and shuttles them through the SCA trapping layer.…”
Section: Resultscontrasting
confidence: 51%
“…We predict that these conditions will lower the extent of protein charging in the presence of SCAs. 18-crown-6 (18C6) is of particular interest due to its ability to accommodate ESI-relevant species (Na + , NH 4 + , and H 3 O + ) in solution and in the gas phase. , Previous studies explored 18C6 binding to Lys + and N + -termini of gaseous peptides or proteins, but the consequences of crown ethers for the ESI process remain largely unexplored . The MD simulations of this work, as well as experiments on proteins and dendrimers, support the proposed hypothesis.…”
supporting
confidence: 62%
“…The extraction combinations of β-diketones, 4-acyl-pyrazolones, or 4-acylisoxazolones with crown ethers have been often used for the extraction of different metals ions. Since 1967, when Pedersen’s pioneering work opened up the field of supramolecular chemistry, there has been a growing interest in crown ethers and their metal complexes in solution. The stability of the crown complexes in solvent extraction depends on the following factors: the size of the crown cavity compared to the cation diameter, the counteranion, ligand flexibility, and the type of the donor groups in the macrocyclic host. , A common feature of synergistic extraction systems is the increased extraction strength, generally at the expense of selectivity. Aly et al found significant enhancement of the extraction and separation with the systems containing Yb(III), Tm(III), and Eu(III) in the presence of DB18C6, 15C5, 12C4, and thenoyltrifluoroacetone (HTTA) in chloroform.…”
Section: Introductionmentioning
confidence: 99%